Effect of Liquid Invasion Damage and Supercharging on Wireline Formation Tester Measurements in Tight Gas Reservoirs - Andrews, J.; Bahrami, Hassan; Rezaee, Reza; Porabed, H.; Mehmood, S.; Salemi, H. (Australian Petroleum Production and Exploration Association, 2012)
Wireline formation testing and measurement of true formation pressure can provide essential knowledge about the reservoir dynamic characteristics. In tight formations, a reliable determination of pressure and mobility gradients is challenging because of the tight nature of formation rock. Due to the very low reservoir permeability, the mud cake across wellbore is often ineffective in preventing filtrate invasion, thus causing the measured pressure to be higher than actual formation pressure as a result of supercharging effect. Wireline formation testing measurements are also influenced by the effects of filtrate invasion and capillary pressure, as the measured pressure is pressure of drilling fluid filtrate, the continuous phase present in the invaded region around wellbore. As a result, the measured pressure might be different to true formation pressure. This effect is more noticeable in tight gas reservoirs due to capillary pressure effect. This paper looks into estimation of true formation pressure and evaluates the effect of filtrate invasion damage and supercharging on wireline formation tester measurements in tight gas reservoirs. Numerical simulation approach is used to build the reservoir model based on data acquired from a tight gas reservoir. The model undergoes water injection followed by gas production from different testing points along the wellbore, and the corresponding pressure gradients are plotted to check for pressure matching with that of the formation fluid in the virgin region. The results indicate the significant effects of supercharging, reservoir characteristics, capillary pressure and liquid invasion damage on wireline formation pressure measurements in tight gas reservoirs.